Sociocultural Specificity of Conceptualization of Environmental Safety in the British Media Space - L. A. Kochetova; M. N. Orlaynskaya (Дискурс)
Introduction. Environmental safety as the most important value of modern society receives multiple and variable embodiment in media discourse, which acts as a powerful factor in influencing and shaping public opinion. The scientific novelty of the study lies in identifying the socio-culturally determined variability of representation of conceptual features of environmental safety in the British media discourse.Methodology and sources. The study was conducted using a corpus of texts devoted to environmental safety, with a volume of over 200 thousand words, as well as using data from the News on Web (NOW) corpus, with a volume of over 1.9 billion words. The content specificity of value in high-quality and popular British media was determined based on the systematization and quantification of collocations with key lexemes that form the cognitivesemantic foundations of the media narrative.Results and discussion. Modeling the conceptual component of the concept of “environmental safety” based on the means of its media representation showed that it includes the conceptualization of threats, risks, causes and sources of threats; negative consequences; actions aimed at combating threats and minimizing risks; subjects of actions that contribute to ensuring safety; objects whose safety must be ensured; necessary actions. Corpus analysis of collocations showed a socio-cultural difference in the discursive representation of environmental safety in the texts of the quality and popular press. The quality press emphasizes global warming, strategies for solving the problem, as well as adaptation to changed conditions and risk minimization; in the popular press, the problem of climate change dominates, while in the quality press the evaluative component of the concept is expanded, and instead of the neutral noun change in combination with the noun climate, the negatively evaluative lexeme crisis is used.Conclusion. The proposed methodology can be used in the analysis of the substantive specificity of other conceptual formations in media discursive practices, in the study of the linguocultural component of the discourse of environmental safety in the aspect of sociocultural and ideological variability.